A PHITS-based computational model of a TRIGA-fueled subcritical reactor for gamma dose mapping - Cruz, Jowi Rapha Pili (Animo Repository, 2023)
Since 1988, the Philippines has lacked access to any nuclear facilities, creating a significant void in the field of study for Filipinos. However, after a hiatus of 34 years, this gap has finally been addressed with the recent authorization granted to the PRR1-SATER, allowing it to resume operations once again. This work involved developing a PHITS-based computational model for the recently commissioned PRR-1 SATER using PHITS. The model utilized a simplified model of the TRIGA fuel that releases photons with 0.6617 MeV energy from the Cs-137 fission product in the fuel. The simulation employed 10E8 particles for photon transport. Compared to previous works on photon transport mapping, which utilizes average source definition, this research utilized individually declared fuel intensities and compared them with the averaged fuel declaration. The different fuel declarations showed that there was a noticeable difference inside the reactor tank which is very relevant for irradiation applications of a research reactor. However, defining the fuel rods by their average strength is sufficient when it comes to radiation protection purposes. The simulation was also done in fuel source intensities based on the average and ± 1 standard deviation of the gamma intensity which shows that the increase/decrease of the fuel strength also increases the gamma dose rate in the whole facility in a similar ratio. Temperature effect is also investigated where the PHITS simulation showed a negligible change of 0.34% for every 2°C increments from 25°C – 35 °C. For 0.5m beyond the reactor tank using cylindrical phantoms, the results confirmed the inherent safety of the reactor tank by using 500 hours as the average working conditions in a year, workers will only receive 1% of the radiation dose limits per year and 4% for the average dose in 5 years set by the Code of PNRI Regulations. Even during a loss of water accident, when compared to the emergency turnback guidance of the IAEA an overly conservative exposure time of 500 hours would only get a total of 45.5% of the dose limit. Lastly, the results were compared to experimental measurements and MCNP v5. PHITS calculations were close to about an average of 98% of the experimental measurements from all cell detectors. When compared to MCNP, MCNP is observed to have a slightly higher calculation of 17% percentage difference.